Difficulties in Treating Dermatophytes: A Way To Overcome - Khan, Zulfiqur Hossain (Bangladesh Journal of Medicine, 2023)
Superficial dermatophytosisis currently caused by dermatophytes belonging to three genera, namely Trichophyton, Microspurum and Epidermophyton. In recent years, superficialmycosis have becomeincreasingly resistant to current antifungal treatment. Multiple incidences of chronic infections, reinfections and treatment failure have been reported. The epidemiological shift from T, rubrumtoT. mentagrophytes/ T. interdigitalis are the dominant pathogen in recent tenea patients. Limitation of available approved antifungals for dermatophytosis treatment and difficulties or unavailability of culture and sensitivity test for fungus also contribute to difficulties in treatment outcome.The change in the clinical scenario with increasing frequency of treatment failure gives rise to innumerate treatment options based on individual experience from case by case. We focus on treatmentschedule given in standard textbooks and the current modifications that have evolved to treat the dermatophytosis. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 193